High‐Resolution On‐Demand Nanostructures. Issue 20 (23rd September 2020) - Schneider, Norbert; Kolew, Alexander; Schneider, Marc; Worgull, Matthias; Gspann, Thurid; Leuthold, Juerg
Abstract : By embedding a film of highly aligned carbon nanotubes (CNTs) into a shape memory polymer (SMP), a fourfold increase in resolution of nanostructures raised on demand with a simple laser pointer is achieved. In the design of nanostructured compounds for micro‐optic and microfluidic lab‐on‐chip and security applications, the SMP's imprinted surface modifications act as the active part, while the CNT film aids their fabrication as an efficient broadband absorber converting light into thermal energy and initializing the polymer's shape memory effect. Due to its extraordinarily high thermal conductivity, the CNT film further acts as a highly efficient heat sink dissipating excess heat before it can blur the boundaries of the raised nanostructures' region. A low‐cost fabrication method of those CNT–SMP compounds is presented and how the programming and recovery properties enable the production of nanoscale surface modifications with unprecedented simplicity, flexibility, and resolution is shown. Abstract : Herein, a versatile high‐resolution, easily activated interchangeable surface topography is presented. A composite material is introduced that enables efficient light absorption and highly localized heat distribution. These favorable effects are achieved by means of a carbon‐nanotube layer embedded in a shape memory polymer matrix. The theoretical basis, the fabrication, and results are presented and discussed.